Identifying trajectories of joint space width loss among previously injured knees: Data from the Osteoarthritis Initiative. - Mary Catherine C Minnig; Liubov Arbeeva; Jennifer L Lund; Stephen W Marshall; Daniel B Nissman; Amanda E Nelson; Yvonne M Golightly (PLoS ONE, 2025)
Objectives To identify trajectories of joint space width loss, a proxy measure of tibiofemoral cartilage loss, among previously injured knees. To describe the relationship of trajectory groups with sociodemographic and clinical risk factors. Methods Using data from the Osteoarthritis Initiative, we identified right knees with a history of injury. We used group-based trajectory modeling to identify trajectories of joint space width loss over 96-months. Once trajectories were identified, we compared baseline statistics of key risk factors across trajectory groups. Results Our primary cohort included 772 previously injured right knees. We also analyzed a subset of 251 more recently injured right knees. Across each cohort, we identified three distinct trajectories for men and women separately, differentiated by low, medium, and high baseline joint space width. Rates of JSW loss were similar between trajectories. Those assigned to the high baseline JSW trajectory were younger at study baseline than those assigned to other two trajectories. Among women assigned to the low baseline JSW group, mean age at the time of knee injury was older than the other two trajectories. Among both men and women, the proportion of knees that had undergone a surgery or arthroscopy was highest in the low baseline JSW group. Conclusions Among knees with a history of injury, thinner JSW may be associated with knee surgical history and older age. Moving forward, exploring additional risk factors for OA development among previously injured knees may provide new opportunities to target treatments towards those at the greatest risk for the disease.